2018
DOI: 10.3748/wjg.v24.i47.5366
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing major venous occlusion and duodenal lesions in rats, and therapy with the stable gastric pentadecapeptide BPC 157, L-NAME and L-arginine

Abstract: AIMTo investigate whether duodenal lesions induced by major venous occlusions can be attenuated by BPC 157 regardless nitric oxide (NO) system involvement.METHODSMale Wistar rats underwent superior anterior pancreaticoduodenal vein (SAPDV)-ligation and were treated with a bath at the ligated SAPDV site (BPC 157 10 μg, 10 ng/kg per 1 mL bath/rat; L-NAME 5 mg/kg per 1 mL bath/rat; L-arginine 100 mg/kg per 1 mL bath/rat, alone and/or together; or BPC 157 10 μg/kg instilled into the rat stomach, at 1 min ligation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(148 citation statements)
references
References 44 publications
11
137
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 81%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 81%
“…113 Similar evidence follows the ligation of the superior anterior pancreaticoduodenal vein and duodenal congestion lesions, which were completely counteracted by BPC 157 application, both with intraabdominal bath or intragastric application with rapid presentation of the bypassing pathway through inferior anterior pancreaticoduodenal vein to superior mesenteric vein. 117 This corresponds to the general evidence that BPC 157 was used in ulcerative colitis trial and duodenal lesions counteraction. [1][2][3][4][5][6][7][8][9][10][11][12][13] As a proof of the integrative healing evidence (rapid cytoprotective endothelium rescue that BPC 157 exerted may be useful against damaging chain of events during ischemia [two ligations] and during reperfusion [ligations removed]) appear normalized NO-and malondialdehyde (MDA)-values in colon tissues, oxidative stress markers.…”
Section: Bpc 157 Stomach Cytoprotection Concept → Wound Heal-supporting
confidence: 53%
See 3 more Smart Citations